Visual acuity and patient satisfaction at varied distances and lighting conditions after implantation of an aspheric diffractive multifocal one-piece intraocular lens - Chang DH (Dove Medical Press, 2016)
Daniel H Chang Empire Eye and Laser Center, Bakersfield, CA, USA Purpose: The aim of the study is to evaluate the visual acuity and patient satisfaction at varied distances under photopic and mesopic lighting conditions in patients bilaterally implanted with aspheric diffractive multifocal one-piece intraocular lenses. Methods: In this retrospective–prospective study, 16 patients with a mean age of 66.2±9.2 years (range: 50–81 years) who had undergone bilateral phacoemulsification surgery with implantation of a Tecnis multifocal one-piece intraocular lens (ZMB00) were evaluated. Monocular and binocular uncorrected and distance-corrected visual acuities were measured at distance (20 ft), intermediate (70–80 cm), and near (35–40 cm) under photopic (85 cd/m2) and mesopic (3 cd/m2) lighting conditions and were compared using the paired t-test. All patients also completed a subjective questionnaire. Results: At a mean follow-up of 9.5±3.9 months, distance, near, and intermediate visual acuity improved significantly from preoperative acuity. Under photopic and mesopic conditions, 93.8% and 62.5% of patients, respectively, had binocular uncorrected intermediate visual acuity of 20/40 or better, and 62.5% and 31.3% of patients had binocular uncorrected near visual acuity of 20/20 or better. All patients were satisfied with their overall vision without using glasses and/or contact lenses when compared with before surgery. A total of 87.5% of patients reported no glare and 68.8% of patients reported no halos around lights at night. Conclusion: Tecnis multifocal one-piece intraocular lenses provide good distance, intermediate, and near visual acuity under photopic as well as mesopic lighting conditions. High levels of spectacle independence with low levels of photic phenomenon were achieved, resulting in excellent patient satisfaction. Keywords: Tecnis multifocal one-piece IOL, photopic visual acuity, mesopic visual acuity, intermediate visual acuity, near visual acuity